2011
DOI: 10.1590/s1519-69842011000100019
|View full text |Cite
|
Sign up to set email alerts
|

Mercury accumulation and metallothionein expression from aquafeeds by Litopenaeus vannamei Boone, 1931 under intensive aquaculture conditions

Abstract: This study describes the accumulation of Hg and metallothionein gene expression in Litopenaeus vannamei Boone, 1931 with aquafeeds as the major source of Hg. Trials were conducted under controlled conditions in experimental tank facilities with high (indoor tanks) and low (outdoor tanks) Hg aquafeeds concentrations. Aquafeeds were the sole source of Hg for the shrimps and concentrations varied from 5.4 to 124 ng.g-1 d.w.. In the three animal fractions analysed; muscle (6,3 - 15,9 ng.g-1); hepatopancreas (5,1 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…There are many examples of higher Hg concentrations in fish liver tissues (Romeo et al, 1999;Mieiro et al, 2009;Guilherme et al, 2010;Azevedo et al, 2012), but a lower Hg liver content was observed in several fish species including sharks (Cizdziel et al, 2003;Kenšová et al, 2010;. This difference coincides with the results obtained by Pethybridge et al (2010) and Le Bourg et al (2014) in embryos of placental and aplacental sharks, and is probably due to a lower content of inorganic than organic Hg, which has a high degree of affinity for the thiol groups of the muscle tissues (Soares et al, 2011).…”
Section: Discussionsupporting
confidence: 78%
“…There are many examples of higher Hg concentrations in fish liver tissues (Romeo et al, 1999;Mieiro et al, 2009;Guilherme et al, 2010;Azevedo et al, 2012), but a lower Hg liver content was observed in several fish species including sharks (Cizdziel et al, 2003;Kenšová et al, 2010;. This difference coincides with the results obtained by Pethybridge et al (2010) and Le Bourg et al (2014) in embryos of placental and aplacental sharks, and is probably due to a lower content of inorganic than organic Hg, which has a high degree of affinity for the thiol groups of the muscle tissues (Soares et al, 2011).…”
Section: Discussionsupporting
confidence: 78%
“…Concentrations of Hg in fish from Ceará vary according to species, size of individuals, trophic level, and geographic origin. In general, most species of river, estuarine and oceanic fishes (Costa and Lacerda, 2014;Lacerda et al, 2016;Moura and de Lacerda, 2018;Moura et al, 2020), as well as aquaculture products (Soares et al, 2011;Oliveira et al, 2015), present Hg contamination below the maximum limits established in the Brazilian legislation (0.5 μg.g − 1 and 1 μg.g − 1 for non-predator and predator fishes, respectively) and, therefore, being safe for human consumption. However, in the case of medium and large oceanic fish, some exceptions may occur.…”
Section: Introductionmentioning
confidence: 96%
“…Body distribution of the incorporated Hg can be heterogeneous, and may vary according to taxon. Within the cells, Hg can form complexes with proteins and accumulate within specific organs; segregated in cytoplasm granules; or transferred to the exoskeleton and discharged during ecdysis within the fragments of the exoskeleton and excreted in fecal pellets (Weeks et al 1992;Soares et al 2011). Regardless of the total Hg present in a given environment, its relative bioavailability is the principal controlling parameter of bioaccumulation.…”
Section: Introductionmentioning
confidence: 99%